Risk Management Analysis Website E-klim at Civil Service Savings and Insurance Using COBIT 4.1 - Muhammad Andhika Prasetyo; Resad Setyadi (SISFORMA, 2022)
Use of Information Technology Governance (ITG). In increasing the speed and accuracy of IT services in the company, as well as increasing the occurrence of risk. With the company's level of dependence on IT services to carry out company operations, a maturity level is needed for the possibilities that occur, aiming to prevent and reduce risks to company assets. This research is based on risk management analysis on the E-klim website which is a system asset at PT TASPEN, so it uses the Control Objective for Information and Relate Technology (COBIT) framework version 4.1. This study applies a quantitative method by distributing questionnaires to obtain good validity and reliability test results. The results of this study indicate the maturity level at level 3, which means define process. The implementation process in the company has been organized and organized in its operational system. However, it is necessary to improve participant administration data and update the system for employees.